Sistem Informasi Berbasis Analisis Persepsi, Pengetahuan, dan Praktik Kesehatan Gigi Pada Anak-Anak Sekolah Dasar - Aditya Ferdiana Arief; Rohmatul Fajriyah; Punik Mumpuni Wijayanti (Universitas Duta Bangsa Surakarta, 2021)
The variety of cases of dental health that occur in elementary school children makes it difficult to quickly identify the factors that most influence dental health. To find out the dental health factors, a system that is able to provide a visual representation of the results of statistical analysis is needed based on the factors that affect oral health in elementary school children. Health information system analysis is mostly done through statistical data analysis. A total of 54 students were included in this study to determine the characteristics, factors that affect dental health, and the implementation of the application in the form of a prototype. The results showed that there was a significant relationship between children's perceptions and their knowledge of dental health and children's perceptions of dental health behavior. Furthermore, guidance and examples from parents play an important role in improving children's behavior regarding dental health. The t-test shows that male students get more examples and attention from their parents regarding dental health. Meanwhile, female students are more concerned with practicing matters related to dental health. The mobile application provides information on children's dental health statistics for schools and health centers. In addition, the application can also provide an overview of dental health in children.